Brazilian union actions for workers’ health protection - Repullo Junior, Rodolpho; Gomes, Jorge da Rocha (São Paulo Medical Journal, 2005)
CONTEXT: Many authors have emphasized the importance of worker strength through unionized organizations, in relation to the improvement of working procedures, and have reported on the decisiveness of labor movement actions in achieving modiﬁcations within the ﬁeld of work and health. OBJECTIVE: To describe the ways in which Brazilian unions have tried to intervene in health-illness and work processes, identifying the existence of commonality in union actions in this ﬁeld. TYPE OF STUDY: Qualitative study. SETTING: Postgraduate Program, Environmental Health Department, Faculdade de Saúde Pública, Universidade de São Paulo, São Paulo, Brazil. METHODS: Union health advisers and directors were interviewed. Documents relating to union action towards protecting workers’ health were collected and analyzed. RESULTS: Unions articulate actions regarding workers’ health of a technical and political nature that involve many aspects and high complexity. These have been divided into thematic categories for better analysis. DISCUSSION: Union actions regarding workers’ health in Brazil are restricted to some unions, located mainly in the southern, southeastern and northeastern regions of the country. Nonetheless, the unions undertaking such actions represent many professions of great economic and political importance. CONCLUSIONS: The recent changes in health and safety at work regulations, recognition of profes- sional diseases, creation of workers’ health services and programs within the uniﬁed health system, and operational improvements in companies’ specialized safety and occupational medicine services, all basically result from union action. There is commonality of union action in this ﬁeld in its seeking of technical and political strengthening for all workers and their general and local representation. This has the objective of beneﬁting collective bargaining between employers and workers. Inter-institutional action on behalf of workers’ rights guarantees and ampliﬁes the improvement of health and working conditions.